Tingkat Kesuburan Muara Tukad Aya, Jembrana Bali Berdasarkan Kelimpahan Plankton dan Ketersediaan Nutrien - Josua Siagian; I Wayan Arthana; Dewa Ayu Angga Pebriani (Current Trends in Aquatic Science, 2019)
River estuaries have characteristics that were directly related to the sea, resulting of mixing water which resulting in a unique in terms of complex and dynamic environment and community structure of biota that was different from other waters. The purpose of this study was to determine the fertility level of Muara Tukad Aya base on the abundance of plankton. This research was conducted in February-March 2019 using descriptive quantitative methods. The average value of water quality in the three stations, namely turbidity ranges from 11.5 to 12.48 NTU, temperature 27.61-31.20C, current speed 0-0.2 m / s, brightness 72.32-86.8 cm, salinity 16.0-17.94 ppt, pH 8.02-8.14, Nitrate 0.5-1.05 mg / L, Phosphate 0.08-0.2 mg / L, DO 7.7- 8.8 (mg / L). The abundance of phytoplankton was found in 37 genera, the total abundance at station I (upstream of the estuary) was 1501 cells / l, at station II (open area of estuary) was 1322 cells / l and station III (close area of the estuary) with an abundance of 833 cells / l. Zooplankton abundance was 6 genera, where total abundance at station I was 9 ind / L, station II was 11 ind / l while station III was 10 ind / l . Water quality parameter values at estuary Tukad are still good and optimum except phosphate levels , The abundance of phytoplankton with nitrite and nitrate has a close relationship with the correlation coefficient -0.9014 and 0.8994.